SERVICE QUALITY ANALYSIS AND IMPROVEMENT: DEVELOPMENT OFA SYSTEMATIC FRAMEWORK - Kim, K-J.; Cho, H-W.; Jeong, I-J.; Park, J-C.; Park, Y-J.; Kim, C-G.; Kim, T-H. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
As the service sector is rapidly growing, one of the challenges faced by the service industry is the lack of effe·ctive methodologies for quality analysis and improvement. In service industries, the service quality serves as both a customer retention tool and a business differentiator in local and global competition. This paper aims at developing a systematic framework for service quality analysis and improvement. The proposed framework advantageously integrates quality function deployment (QFD) and structural equation modeling (SEM). More specifically, the framework utilizes QFD to collect, organize, and analyze qualitative information. The results of QFD are used as the basis for developing a service quality improvement strategy. Then, SEM is used in building and analyzing quantitative models to devise a detailed strategy for the improvement. The proposed framework is demonstrated through a case study on the asymmetric digital subscriber lines (ADSL) service of a major telecommunication company in Asia. This framework can be utilized for an effective analysis and improvement ofservice quality not just in the telecommunication industry, but also in any service industry which collects customer satisfaction and service performance data as part of its daily operation.